The Role of the Glass Ceiling on Organizational Commitment of Female Academic Staff in Jordanian Higher Education Institutions - Tawalbeh, Mohammad; Tawalbeh, Jawad (Journal of Ecohumanism, 2024)
The current study examined the role of the glass ceiling on the organizational commitment of female academic staff in Jordanian Higher Education Institutions. Workplaces dominated by gender discrimination and a glass ceiling tend to have employees with less organizational commitment and lose experienced, and knowledgeable female talent. 245 participants were included in the study and asked to rate their level of agreement using a Likert scale on multiple statements regarding their perspectives/beliefs on two questionnaires (glass ceiling and organizational Commitment). Our findings indicated that there is a negative correlation between three dimensions of the glass ceiling; family barriers (r= - 0.68), social barriers (r= - 0.51) organizational barriers (r= - 0.77) and organizational commitment were significant. Among the dimensions of the glass ceiling, family barriers and organizational barriers were the best predictors of organizational commitment.